2009
DOI: 10.1002/anie.200806000
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral DNA Nanocapsules by Modular Assembly

Abstract: It's a trap! DNA polyhedra formed through molecular self-assembly may function as nanocapsules for the targeted delivery of encapsulated entities. This functional aspect was demonstrated for the most complex DNA-based platonic solid: During the stepwise amalgamation of discrete polyhedra to form icosahedra, gold nanoparticles (GNPs) were encapsulated from solution (see illustration and TEM image of icosahedral cages containing GNPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
171
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 23 publications
2
171
0
3
Order By: Relevance
“…[4,5] Furthermore, it has been shown that DNA can be designed to organize into extended arrays, such as 2D [6] and 3D crystals. [7,8] Branching points have so far been incorporated in these materials by including DNA four-way ("Holliday") junctions or by covalent modification.…”
mentioning
confidence: 99%
“…[4,5] Furthermore, it has been shown that DNA can be designed to organize into extended arrays, such as 2D [6] and 3D crystals. [7,8] Branching points have so far been incorporated in these materials by including DNA four-way ("Holliday") junctions or by covalent modification.…”
mentioning
confidence: 99%
“…For example, there have been various reports of the assembly of hollow DNA cages to encapsulate nanoparticles [65][66][67] and proteins, [68,69] other carriers that display cargo molecules on their surface, [70] and simple double-helical structures that intercalating drugs can be loaded into. [71,72] Meanwhile, because DNA objects can function as reconfigurable nanomachines, [14,68] it is expected that DNA nanostructures can be translated into controllable drug-release vehicles.…”
Section: Functionalized Dna Nanostructures For Disease Treatmentmentioning
confidence: 99%
“…Differently, Krishnan et al reported a stochastic encapsulation of gold nanoparticles from solution in a DNA icosahedron formed in-situ, by complexing two half-icosahedra bearing complementary overhangs. [61] Each of the icosahedral halves was a self-assembled product of six 5-way junctions (two of which were unique).…”
Section: D Scaffolded Organizationmentioning
confidence: 99%